Bridging East and West: Re-examining the notion of corporate governance in explaining institutional change - Michal Federowicz (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
The paper discusses the theoretical framework for cross-national research on corporate governance. Although the field of corporate governance is largely explored, the existing analyses focus rather on advanced economies and detailed comparisons between them, and sometimes try to apply the same theoretical framework to other countries. However, the development of a sound governance structure in 'catching-up' economies is typically affected by the political process of reforms. Quite often informal institutions, which still exist in the political proceedings, undermine formal settings of governance existing in these countries. The paper starts with the assumption that considerations of corporate governance in the .East - West. comparisons can not neglect a broad perspective of the political nature of governance arrangements both formal and informal. It also examines the adequacy of 'path-dependency' approaches. It adds to the perspective of .Varieties of Capitalism. some dimensions which make this perspective more sensitive towards .East - West. analyses.
Keywords: 300; Corporate Governance; Systemvergleich; Systemtransformation; Institutioneller Wandel; Westliche Staaten; Osteuropa